Working with the Private Sector for Child Health - Waters, Hugh (World Bank, Washington, DC, 2013)
This document assesses the current importance and potential of the private sector in contributing to child health. In many countries private and non-governmental providers are more commonly consulted for child health illnesses than public providers are. Even poor families often use private sector services. Families spend relatively large amounts of money for curative services in the private sector, even when there are cheaper public sector alternatives available. However, in many settings private providers are poorly regulated and the technical quality of the services they provide is questionable. This document focuses on the role of the private sector in the direct provision of child health services. The private sector clearly has a much broader potential role in many other areas related to and supporting the provision of child health services-including the provision of ancillary services, training of health professionals (both pre-service and in-service), communication services, and financing of health care. The potential of the private sector in each of these areas is touched on in this document, but a detailed treatment of each of these important topics is beyond the scope of the paper. Financing of health care and services is a particularly complex topic. In most countries, the private sector has an important role to play in financing both recurrent health service costs and investment costs.